Neferine Ameliorates Sepsis-Induced Myocardial Dysfunction Through Anti-Apoptotic and Antioxidative Effects by Regulating the PI3K/AKT/mTOR Signaling Pathway - Qi, Zhen; Wang, Renrong; Liao, Rongheng; Xue, Song; Wang, Yongyi (Frontiers in Pharmacology, 2021)
Septic cardiomyopathy is a common complication of severe sepsis, which is one of the leading causes of death in intensive care units. Therefore, finding an effective therapy target is urgent. Neferine is an alkaloid extracted from the green embryos of mature seeds of Nelumbo nucifera Gaertn., which has been reported to exhibit various biological activities and pharmacological properties. This study aims to explore the protective effects of neferine against lipopolysaccharide (LPS)-induced myocardial dysfunction and its mechanisms. The LPS-induced cardiac dysfunction mouse model was employed to investigate the protective effects of neferine. In this study, we demonstrated that neferine remarkably improved cardiac function and survival rate and ameliorated morphological damage to heart tissue in LPS-induced mice. Neferine also improved cell viability and mitochondrial function and reduced cell apoptosis and the production of reactive oxygen species in LPS-treated H9c2 cells. In addition, neferine significantly upregulated Bcl-2 expression and suppressed cleaved caspase 3 activity in LPS-induced mouse heart tissue and H9c2 cells. Furthermore, neferine also upregulated the phosphatidylinositol 3-kinase/protein kinase B/mechanistic target of rapamycin (PI3K/AKT/mTOR) signaling pathway in vivo and in vitro. Conversely, LY294002 (a PI3K inhibitor) reversed the protective effect of neferine in LPS-induced H9c2 cells. Our findings thus demonstrate that neferine ameliorates LPS-induced cardiac dysfunction by activating the PI3K/AKT/mTOR signaling pathway and presents a promising therapeutic agent for the treatment of LPS-induced cardiac dysfunction.